The homeless student – and recovering a sense of belonging - Barnett, Ronald (Journal of University Teaching and Learning Practice, 2022)
There is much empirical evidence to suggest that many students today feel alone and experience anxiety. These phenomena – loneliness and anxiety - have long existed but there is reason to believe that they are heightened in the twenty-first century; and universities are putting in effort to alleviate levels of student stress. However, largely missing is a sense that a degree of destabilization is necessary for an educational process to be worthy of the name of ‘higher education’. It is part of higher education that a student should be, to some extent, epistemologically unsettled. And that unsettlement has to include students becoming reflective of their taken-for-granted frameworks and recognizing the contingency of those frameworks. The student comes ultimately and continually to unsettle her/himself. Higher education, accordingly, is a site of homelessness, in which students embark on a process of permanent – that is, lifelong – self-unsettlement. Fundamentally, therefore, a genuine higher education is not so much a matter of acquiring knowledge (an epistemological process) or skills (a practical process) but about taking on a nomadic form of being (an ontological process); a being always on the move. The student develops a will to unlearn and comes even to revel in it. It is a responsibility of the university to provide the institutional and the pedagogical wherewithal to elicit this kind of student homefulness even alongside a continuing homelessness.